Representations of some MD5-group via deformation quantization - Nguyen, Viet Hai (H. : ĐHQGHN, 2017)
The present paper is a continuation of Nguyen Viet Hai’s ones [3], [4], [6], [7]. Specifically, the paper is concerned with the subclass of connected and simply connected MDs-groups such that their MDs-algebras Q have the derived ideal Gl := [Q,G] R3. We show that the ^-representations of these MDs-algebras result from the quantization of the Poisson bracket on the coalgebra in canonical coordinates.